Preparation of nearly monodisperse nickel nanoparticles by a facile solution based methodology and their ordered assemblies - Sidhaye, Deepti S.; Bala, Tanushree; Srinath, S.; Srikanth, H.; Poddar, Pankaj; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2009)
Nickel nanoparticles have been synthesized by a simple wet chemical reduction technique in the presence of a surfactant sodium dodecyl sulfate (SDS) and a capping agent oleic acid. Varying the concentration of the surfactant and the capping agent has been found to critically govern the nature of the nanoparticles prepared. It is observed that at an optimum concentration of SDS and oleic acid, nearly monodisperse Ni nanoparticles are obtained that form highly ordered hexagonally close-packed structures on electron microscopy grids by a simple drop coating procedure. It is also shown that the presence of oleic acid is necessary for the stability of the Ni nanoparticles synthesized. Structural and magnetic characterizations of the nanoparticles are also presented.